Numerical Simulations of the SEIR Epidemiological Model with Population Heterogeneity to Assess the Efficiency of Social Isolation in Controlling COVID-19 in Brazil - Soares, A. L. O.; Caloi, C. M.; Bassanezi, R. C. (Trends in Computational and Applied Mathematics, 2022)
On 30 January 2020, the World Health Organization (WHO) officially declared the epidemic of Coronavirus (COVID-19), which is a highly contagious virus that has been causing deaths worldwide. Early treatment was proven to be inefficient and social isolation became the main factor inhibiting the disease, before vaccination. In this article, we evaluate the efficiency of this isolation as a control, through numerical simulations of mathematical model of the SEIR type (Susceptible-Exposed-Infectious-Removed) with population heterogeneity, in which the susceptible population was distributed according to the age group (children / youth, adults and elderly) and the infectious population was categorized according to the severity of symptoms (severe, mild and asymptomatic). The results suggest that the isolation of only one of the susceptible subpopulations is inefficient to control the spread of the virus, which indicates that vertical isolation is not enough to contain the proliferation of COVID-19. Furthermore, the disease does not have the strength to invade the population when there is sufficient social isolation composed of susceptible subpopulations and the epidemiological scenario improves when there is awareness of the importance of the quarantine of infectious individuals with mild symptoms.